The cervical sagittal curvature change in patients with or without PCSM after laminoplasty - Qian, Shengjun; Wang, Zhan; Ren, Ying; Chew, Ian; Jiang, Guangyao; Li, Wanli; Chen, Weishan (Frontiers in Surgery, 2022)
Objective: After laminoplasty, the cervical sagittal curvature of some patients tend to be lordotic, this phenomenon cannot be explained by the theory of laminoplasty, and the reason remains unknown. We explored the possible role played by pinching cervical spondylotic myelopathy (PCSM) in the cervical sagittal curvature change in patients after laminoplasty. Methods: From April 2017 to May 2019, we studied 122 patients undergoing laminoplasty with cervical spondylotic myelopathy (CSM). All patients were divided into Group A (anterior compression only, without PCSM) and Group B (both anterior and posterior compression, with PCSM). The visual analogue scale (VAS) was used to measure pain, and modiﬁed Japanese Orthopedic Association (mJOA) score was derived. The cervical global angle (CGA) and the range of cervical motion (ROM) were compared. The clinical and imaging results were compared between Group A and Group B. Results: After laminoplasty, both the mean VAS and mJOA scores improved significantly in Group A and Group B, the mJOA recovery rate of Group B was better than that of Group A (P < 0.05). The mean CGA and ROM decreased in Group A, but increased in Group B. MRI revealed that the ligamentum flavum of Group A was significantly thinner than that of Group B (P < 0.05). Conclusions: Because of the hypertrophic and folded ligamentum flavum compressing the dorsal spinal cord, patients with PCSM may maintain a compulsive kyphotic posture. After laminoplasty, the cervical sagittal curvature of these patients tend to be lordotic due to the release of dorsal spinal cord compression.